Wheat Mill Stream Properties for Discrete Element Method Modeling - Patwa, Abhay; Ambrose, R. P. Kingsly; Dogan, Hulya; Casada, Mark E. (My University, 2014)
A discrete phase approach based on individual wheat kernel characteristics is needed to overcome the limitations of previous statistical models and accurately predict the milling behavior of wheat. As a first step to develop a discrete element method (DEM) model for the wheat milling process, this study determined the physical and mechanical properties of wheat mill streams (wheat kernels, break stream, and wheat flour) required as input parameters. The parameters measured were particle size and size distribution, bulk density, Young’s modulus, static and rolling coefficients of friction, and coefficient of restitution. The effect of moisture content (12% to 16% wet basis) on these properties was evaluated. The density, Young’s modulus, and coefficient of restitution tended to decrease while the coefficients of friction tended to increase with increasing moisture content of wheat kernels. The effect of moisture content on material properties was significant for break stream, but there was no significant (p > 0.05) material property change with moisture content for flour. It was concluded that moisture content had a greater significant effect on physical properties (bulk, true, and tapped densities and particle size) of the mill streams than it did on the mechanical properties (Young’s modulus, coefficients of static and rolling friction, and coefficient of restitution).
Keywords: Moisture content; Physical properties; Wheat flour; Wheat mill streams